New infant formulas for healthy term infants: A randomized, controlled, double-blind, multicenter, non-inferiority design safety study - Stephen A. Fleming; Stefanie Flunkert; Anne S. Kvistgaard; James McGrath; David K. Glover (PLoS ONE, 2025)
Objectives Two infant formulas with unique combinations of 1,3-dioleoyl-2-palmitoyl-sn-glycerol sn2 palmitate, galactooligosaccharide, polydextrose, fructooligosaccharide, β-carotene, lutein, α-lactalbumin, osteopontin, and lactoferrin were evaluated for non-inferiority compared to a commercially available formula. Methods In a randomized, controlled, parallel-arm, double-blind, multicenter, non-inferiority study, eligible infants were enrolled to receive an experimental (BBN-001 [Part 1; N = 129], BBN-102 [Part 2; N = 117]) formula or commercial formula (Brand; N = 143) for 120 days (Clinical Trials.gov NCT03331276). Infants were considered eligible if they were healthy, term (≥ 37 and ≤ 42 weeks of gestation), singleton newborns, with a birth weight of at least 2,500 g, and no more than 14 postnatal days-of-age. Anthropometric growth, formula intake, gastrointestinal tolerance, and adverse events were measured throughout the study, and fecal soap fatty acids were measured at the end. The primary endpoint was weight gain at the end of the trial, with treatment groups to be considered non-inferior if their weight gain was > −3 g/d compared to the control group. Results Both experimental formulas were non-inferior to the Brand formula according to anthropometric outcomes. Formula intake, total adverse events, and stool frequency and consistency were similar to Brand formulas. Some measures of gassiness and fussiness improved in the experimental formulas ( P < 0.05). Fecal calcium increased and fecal palmitic acid soaps decreased in both experimental formulas (all P ≤ 0.045), and total soap fatty acids were decreased in the BBN-102 group compared to the Brand group ( P = 0.020). Conclusions The experimental formulas were well tolerated and deemed non-inferior to those of a Brand formula. The experimental formulas improved some measures of gastrointestinal tolerance compared to standard commercially available infant formulas. Trial registration ClinicalTrials.gov NCT03331276